KOMUNIKASI TERBUKA GUNA MENGATASI TOXIC PARENTING SEBAGAI PENDUKUNG UTAMA KESEHATAN MENTAL ANAK DALAM TEKNOLOGI & MEDIA BARU - Rahayu, Muthia (Universitas Mercu Buana, 2024)
The Role of Family can shape children's attitudes and personalities, and can also determine the educational process children receive, not only in school but through all factors that can be sources of education. Family, school, society, and exposure to social media content play important roles in children's mental health. In toxic parenting patterns, parents treat their children disrespectfully as individuals, for example, by not praising the child's work or belittling the things the child has done in daily life. Or parents who like to compare their children with others or with their own siblings, leading to a decrease in the child's self-confidence. In this study, the researcher uses the post-positivism paradigm. The researcher employs a Case Study method with a Qualitative approach. The subjects of this research are fathers, mothers, and children from families in Jakarta and Tangerang from different generation gaps, namely: baby boomers, generation X, generation Y or millennials, and generation Z. The result of this research is that new technologies and media can be effective tools in supporting open family communication. Digital communication platforms such as instant messaging apps and video calls allow parents and children to communicate more easily and regularly, especially if they are not always at home at the same time. Additionally, there are many online resources such as articles, videos, and forums that provide information and support on positive parenting and how to overcome toxic parenting. Social media can also serve as a platform to share experiences and receive support from a wider community.